Light-Sensitive Polymeric Nanoparticles Based on Photo-Cleavable Chromophores - Klinger, Daniel; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2013)
The triggered release of functional compounds from such polymeric carriers as micelles, nanoparticles or nanogels is a rapidly developing and highly versatile concept which is expected to be one of the key approaches to future therapeutics. In his thesis, Daniel Klinger highlights the approach of stimuli-responsive microgels for such applications and discusses why especially light as a trigger has an outstanding position amongst the family of conventional stimuli. Based on these considerations, the author focuses on the design, synthesis and characterization of novel photo-sensitive microgels and nanoparticles as potential materials for the loading and light-triggered release/accessibility of functional compounds. Starting from the synthesis of photo-cleavable organic building blocks and their use in the preparation of polymeric nanoparticles, continuing to the examination of their loading and release profiles, and concluding with biological in vitro studies of the final materials, Daniel Klinger$1 (Bs work is an excellent example of the multidisciplinary research needed for the successful development of new materials in this field and has led to a number of further publications in internationally respected journals.s
Introduction -- Motivation -- Theoretical Part -- Outline -- Results and Discussion -- Conclusion and Outlook -- Experimental Part.
Keywords: Chemistry; Polymers; Nanotechnology; Chemistry; Polymer Sciences; Nanotechnology; Nanoscale Science and Technology